Intestinal Atresia : A Case Report (Journal of Paediatric Surgeons of Bangladesh, 2015)
The outcome of intestinal atresia following surgical repair is very good. In general, morbidity and mortality depend upon type of atresia, level of atresia and associated medical conditions such as prematurity or cystic fibrosis, other congenital anomalies, the complexity of the lesion, and surgical complications (anastomotic leakage, functional obstruction at the site of anastomosis).1- 2 But complete management of these patient is difficult. We managed a patient with type-IIIa ileal atresia, the outcome of which was excellent.J. Paediatr. Surg. Bangladesh 3(2): 85-87, 2012 (July)